Hubungan Durasi Tidur Malam Hari dengan Siklus Menstruasi pada Siswi SMP Kelas IX - Koloay, Chelsea H. J.; Engka, Joice N. A.; Marunduh, Sylvia R. (Medical Scope Journal, 2026)
Abstract: Sleep is an important physiological process for energy recovery and hormonal balance, including maintaining a regular menstrual cycle. Hormonal imbalances caused by lack of sleep can lead to menstrual disorders such as oligomenorrhea and amenorrhea. Teenagers' sleep duration often decreases due to school activities and smartphone use, which can affect the hormonal system. Previous studies have shown inconsistent results regarding the relationship between sleep duration and the menstrual cycle. Therefore, this study aims to determine the relationship between nighttime sleep duration and the menstrual cycle in ninth-grade female students at SMP Negeri 1 Manado. This was  a quantitative observational and analytical study using a cross-sectional design. Data were obtained through the Sleep Timing Questionnaire (STQ) and a menstrual cycle questionnaire distributed via Google Forms. Data analysis was performed using the chi-square statistical test. The results showed that most respondents had insufficient nighttime sleep duration (70.5%) and regular menstrual cycles (61.4%). The chi-square statistical test showed no significant relationship between nighttime sleep duration and menstrual cycle, with a p-value of 0.052. In conclusion, there is no significant relationship between the duration of nighttime sleep and the menstrual cycle in ninth-grade female students at SMP Negeri 1 Manado. Keywords: nighttime sleep duration; menstrual cycle; junior high school students    Abstrak: Tidur merupakan proses fisiologis penting bagi pemulihan energi dan keseimbangan hormonal, termasuk dalam menjaga keteraturan siklus menstruasi. Ketidakseimbangan hormon akibat kurang tidur dapat menyebabkan gangguan menstruasi seperti oligomenore dan amenore. Durasi tidur remaja sering berkurang karena aktivitas sekolah dan penggunaan smartphone yang dapat memengaruhi sistem hormonal. Penelitian terdahulu menunjukkan hasil yang belum konsisten mengenai hubungan durasi tidur dan siklus menstruasi. Penelitian ini bertujuan untuk mengetahui hubungan antara durasi tidur malam hari dengan siklus menstruasi pada siswi kelas IX SMP Negeri 1 Manado. Jenis penelitian kuantitatif yang bersifat observasional analitik dengan desain potong lintang. Data diperoleh melalui Sleep Timing Questionnaire (STQ) dan kuesioner siklus menstruasi yang dibagikan melalui Google Form. Analisis data dilakukan menggunakan uji chi-square. Hasil penelitian mendapatkan sebagian besar responden memiliki durasi tidur malam hari yang kurang (70,5%) dan siklus menstruasi yang teratur (61,4%). Uji statistik chi-square menunjukkan tidak terdapat hubungan bermakna antara durasi tidur malam hari dengan siklus menstruasi dengan nilai signifikansi p=0,052. Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara durasi tidur malam hari dengan siklus menstruasi pada siswi kelas IX di SMP Negeri 1 Manado. Kata kunci: durasi tidur malam hari; siklus menstruasi; siswi SMP